Pengaruh Permainan Finger Painting Terhadap Perkembangan Kreativitas Anak di PAUD Pelita Harapan Pasar Latong - Safrida Harahap; Rani Astria Silvera Harahap; Mira Yanti Lubis (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to find out: (1) Development of children's creativity at PAUD Pelita Harapan Pasar Latong, (2) the influence of finger painting games on the development of children's creativity at PAUD Pelita Harapan Pasar Latong. This research uses a quantitative approach with an experimental research type. The research design used a one-group pretest-posttest type pre-experiment . The instruments used consisted of observation and documentation. The data analysis technique used descriptive statistics and conducted a requirement test, namely normality test and homogeneity test. Hypothesis testing using the